Evaluation of Water‐Energy‐Food (WEF) Nexus Research: Perspectives, Challenges, and Directions for Future Research. (22nd November 2021) - Sušnik, Janez; Staddon, Chad
Abstract: In 2018, Albrecht et al., published a comprehensive review of water‐energy‐food nexus literature, coming to five main criticisms in nexus research based on their perception of the state‐of‐the‐art. The five central conclusions of that review together with a consideration of more recent initiatives form the basis for this critical review. The current state of nexus research, and in particular modeling research, is examined and updated to reflect recent advances, correct some misperceptions, and put the nexus enterprise into the context of larger epistemological issues. The main conclusions of this review are: The considerable and growing diversity in nexus studies necessarily precludes a one‐size‐fits‐all approach, and indeed it has never been an objective to develop a "grand unified nexus theory or model." A lack of "fundamental equations" between many nexus parameters hinders full quantification of all nexus linkages, though data‐driven, stochastic, and agent‐based approaches offer useful avenues for further development. The use of qualitative and social science methods in nexus studies is rapidly gaining traction, especially when blended with quantitative modeling. Great progress has been made in attempting to break disciplinary siloes, especially when considering integrated assessment models and system dynamics models. The paper concludes with some reflections on how progress to date could inform new initiatives, such as the Sustainable Urban Nexus Project, and future work more generally. These reflections are summarized as follows: Integration of ecosystem services and their relationships to the nexus should be a priority in near‐future nexus research efforts. Social science techniques blended with quantitative modeling efforts, and local stakeholder engagement, are critical to the success and impact of nexus studies and their recommendations. Policy‐relevant recommendations are starting to be developed. Greater focus, and stakeholder involvement, will further the policy impact of nexus studies.